2019
DOI: 10.1093/mnras/stz1718
|View full text |Cite
|
Sign up to set email alerts
|

Vortex instabilities triggered by low-mass planets in pebble-rich, inviscid protoplanetary discs

Abstract: In the innermost regions of protoplanerary discs, the solid-to-gas ratio can be increased considerably by a number of processes, including photoevaporative and particle drift. MHD disc models also suggest the existence of a dead-zone at R 10 AU, where the regions close to the midplane remain laminar. In this context, we use two-fluid hydrodynamical simulations to study the interaction between a low-mass planet (∼ 1.7 M ⊕ ) on a fixed orbit and an inviscid pebble-rich disc with solid-to-gas ratio 0.5. For pebbl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…This instability generates vortices at the location of steep density gradients. Such steep gradients are induced by planetary gaps formed at low viscosity (Hammer et al 2017;Pierens et al 2019), as we can see on the radial density profiles in the lower panel of Fig. 9.…”
Section: Different Viscositiessupporting
confidence: 54%
“…This instability generates vortices at the location of steep density gradients. Such steep gradients are induced by planetary gaps formed at low viscosity (Hammer et al 2017;Pierens et al 2019), as we can see on the radial density profiles in the lower panel of Fig. 9.…”
Section: Different Viscositiessupporting
confidence: 54%
“…Because gap edges are also pressure bumps, similar instabilities could happen at dusty rings induced by planets including dust feedback. Pierens et al (2019) showed interactions between a low-mass planet and an inviscid pebble-rich disk. They found that a RWI-liked instability happens at gap edges of planet and a lot of dusty vortices emerged in their simulations.…”
Section: Origin Of Instabilitymentioning
confidence: 99%
“…separatrix in the disc with St = 10 −2 . This results from the scattering of librating, co-orbital dust by the planet whenever it undergoes horseshoe turns, leading to the formation of overdense dust flow at the downstream separatrix (Morbidelli & Nesvorny 2012; Benítez-Llambay & Pessah 2018; Pierens et al 2019). When the metallicity in the co-orbital ring is high, feedback from the scattered, overdense flow can significantly modify the local gas azimuthal velocity, as shown in the top panels of Fig.…”
Section: Disc Morphologymentioning
confidence: 99%
“…The formation of planet-induced dust vortices via RWI-like processes (i.e. edge instabilities) can depend on resolution and viscosity (Chen & Lin 2018;Pierens et al 2019). Here, we perform additional simulations with different resolutions and viscosities to study their effects on planet migration.…”
Section: Effects Of Viscosity and Resolutionmentioning
confidence: 99%
See 1 more Smart Citation